A pregnant with markedly elevated alkaline phosphatase: a case report - Alqralleh, Muna; Al-Hajjaj, Maher; Alasfoor, Sadiq; Salman, Zainab; Salman, Farah Bilal Mohammad; Banihani, Majd J (Clinical Journal of Obstetrics and Gynecology, 2023)
Alkaline Phosphatase (ALP) is produced from the liver, kidney, bone and placenta. During pregnancy, ALP may raise markedly with no clear reason. Here, we present a rare case of highly elevated ALP in a 21 years old pregnant woman during the third trimester who had no important past medical history. It was 2800 U/L. Bone, renal, or liver was all normal. Close monitoring of the fetus and his mother until birth was the way of treatment. We had seven weeks postpartum to decline in ALP concentration but did not return to the normal range. The placenta showed lesions of chronic villitis. The extreme incline in ALP during the gestational stages is riskier because the threat here is posed to 2 lives. In such conditions, constant monitoring of ALP in the maternal serum backed with necessary medication is required.